Legal Authority Crisis in Indigenous Forest Management: The Relationship between Dayak Customary Law and State Law in Kalimantan - Musrifah, Musrifah; Syarifah, Hanni Naylatus (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
The crisis of legal authority in the management of customary forests reflects deep-seated issues in the relationship between customary law and state law in Indonesia, particularly in the context of the Dayak indigenous community in Kalimantan. This research aims to identify and analyze the dynamics of legal conflicts and authority imbalances in forest management recognized as customary areas by local communities, but often claimed as state forest areas by the government. Using a descriptive-analytical qualitative approach and case study method, this research focuses on two strategic areas, namely Lamandau Regency and Gunung Mas. Data were collected through in-depth interviews, field observations, and analysis of legal documents as well as customary territory maps from BRWA and AMAN. The research results indicate that the tension between customary law and state law is evident both structurally and in practice. On one hand, indigenous communities uphold principles of management based on local wisdom, spirituality, and social collectivism; on the other hand, the state imposes a positive law approach and administrative logic on forest areas. This conflict not only creates legal uncertainty but also marginalizes the role of indigenous communities as key stakeholders. The findings also indicate the existence of resistance efforts undertaken by indigenous communities through participatory mapping, strategic litigation, and strengthening local institutions. This research concludes that an approach of legal pluralism and substantial recognition of customary legal authority is a crucial step in creating ecological and social justice for indigenous communities.